Palmitate impairs autophagic degradation via oxidative stress/perilysosomal Ca2+ overload/mTORC1 activation pathway in pancreatic β cells - Nguyen, Ha Thu; Ly, Luong Dai; Ngo, Thuy Thi Thanh; Lee, Soo Kyung; Noriega Polo, Carlos ; 0000-0002-6551-8172; Lee, Subo; Lee, Taesic; Cha, Seung-Kuy; Yasasilka, Xaviera Riani; Cho, Kae Won; Lee, Myung-Shik; Wiederkehr, Andreas; et al. (JCI Insight, 2025)
Saturated fatty acids impose lipotoxic stress on pancreatic β cells, leading to β cell failure and diabetes. In this study, we investigate the critical role of organellar Ca2+ disturbance on defective autophagy and β cell lipotoxicity. Palmitate, a saturated fatty acid, induced perilysosomal Ca2+ elevation, sustained mTOR complex 1 (mTORC1) activation on the lysosomal membrane, suppression of the lysosomal transient receptor potential mucolipin 1 (TRPML1) channel, and accumulation of undigested autophagosomes in β cells. These Ca2+ aberrations with autophagy defects by palmitate were prevented by an mTORC1 inhibitor or a mitochondrial superoxide scavenger. To alleviate perilysosomal Ca2+ overload, strategies such as lowering extracellular Ca2+, employing voltage-gated Ca2+ channel blocker or ATP-sensitive K+ channel opener, effectively abrogated mTORC1 activation and preserved autophagy. Furthermore, redirecting perilysosomal Ca2+ into the endoplasmic reticulum (ER), with an ER Ca2+ ATPase activator, restored TRPML1 activity, promoted autophagic flux, and improved survival of β cells exposed to palmitate-induced lipotoxicity. Our findings suggest oxidative stress/Ca2+ overload/mTORC1 pathway involvement in TRPML1 suppression and defective autophagy during β cell lipotoxicity. Restoring perilysosomal Ca2+ homeostasis emerges as a promising therapeutic strategy for metabolic diseases.
Keywords: Mechanistic Target of Rapamycin Complex 1/metabolism; Insulin-Secreting Cells/metabolism; Oxidative Stress/drug effects; Animals; Lysosomes/metabolism; Autophagy/drug effects; Calcium/metabolism; Mice; Transient Receptor Potential Channels/metabolism; Palmitates/pharmacology; Endoplasmic Reticulum/metabolism; Signal Transduction/drug effects; Humans